Mask Material Filtration Efficiency and Mask Fitting at the Crossroads: Implications during Pandemic Times - Karin Ardon-Dryer; Juliusz Warzywoda; Rumeysa Tekin; Jnev Biros; Sharilyn Almodovar; Brandon L. Weeks; Louisa J. Hope-Weeks; Albert Sacco (Aerosol and Air Quality Research)
Abstract The COVID-19 pandemic triggered the widespread use and need for respirators and face masks for the healthcare workers and public. In this study, several generally available respirators and mask designs were fit tested, and their materials were evaluated for filtration efficiency using 250 nm polystyrene latex particles. Efficiency testing was performed for 2 and 0.5 h at low (2.6 L min−1) and high (7.4 L min−1) airflows, respectively, using ~17.4 cm2 material area. As expected, all N95 and KN95 respirators passed the fit test, and their materials showed efficiencies > 95% for the entire experiment at both airflows. Of the three air filters used in the 3D-printed Montana masks, only the HEPA filter had a filtration efficiency > 95% at both airflows. Regardless of the insert material, the Montana mask failed all fit tests. Homemade duckbill masks made of Halyard H600 sterilization wrap and WypAll X80 reusable wipe also failed the fit test, and both filter materials had an average filtration efficiency < 95% at high airflows. To explain the filtration efficiency results, the structure and composition of all filter materials were determined using FE-SEM, and IR and Raman spectroscopy. In conclusion, when highly efficient materials are used in masks that do not fit the users properly, the potential of these materials to protect the users from aerosols is compromised. Therefore, the mask design is as important as the filtration efficiency of the mask material.